A Cross-cultural Analysis of the Utilization and Efficacy of Traditional Herbal Medicine to Cure High Blood Pressure Among People of Rawalakot - Minahil Javaid; Muhammad Zubair Khan (International Journal of Biochemistry and Biomolecule Research, 2024)
Safety and efficacy of herbal medicines have not yet been established in treating hypertension. The current study examined the prevalence of herbal medicine use among hypertensive patients in Rawalakot, Poonch, Azad Jammu and Kashmir. The study included 100 hypertensive patients using systemic random sampling. The independent variables were herbal medicine and conventional medicine, while the dependent variable was hypertension. The most known and used herbal medicine was garlic followed by ginger and onion. Among the female respondents, garlic was the most frequently cited herbal remedy for high blood pressure, with 44 mentions. This was followed by ginger (16 mentions), onion (15), watercress (14), and coriander (11). 61 of the patients showed strong belief in herbal medicine efficacy against hypertension while 39 disagreed. The younger respondents were found less in their belief and use of herbal remedies. Unemployed, and government-employed respondents were found more frequent cases of hypertension followed by people doing their own business. Similarly, those less educated were the higher cases of hypertension. Most respondents not engaging in daily exercise were found among both male and female participants, with 46 out of 100 not adhering to a daily exercise routine. In contrast, only 16 respondents reported following a regular exercise pattern. Higher systolic and diastolic blood pressure levels were reported by respondents with greater body weight. Herbal medicines were perceived to have varying degrees of effectiveness in controlling blood pressure among hypertensive patients who solely relied on herbal remedies and those who combined them with conventional treatments.
Keywords: Blood Pressure; Ginger; Onion; Rawalakot; garlic; herbal medicine; hypertension